Auditory Survey of Endangered Eurasian Bittern Using Microphone Arrays and Robot Audition - Matsubayashi, Shiho; Nakadai, Kazuhiro; Suzuki, Reiji; Ura, Tatsuya; Hasebe, Makoto; Okuno, Hiroshi G. (Frontiers in Robotics and AI, 2022)
Bioacoustics monitoring has become increasingly popular for studying the behavior and ecology of vocalizing birds. This study aims to verify the practical effectiveness of localization technology for auditory monitoring of endangered Eurasian bittern (Botaurus stellaris) which inhabits wetlands in remote areas with thick vegetation. Their crepuscular and highly secretive nature, except during the breeding season when they vocalize advertisement calls, make them difficult to monitor. Because of the increasing rates of habitat loss, surveying accurate numbers and their habitat needs are both important conservation tasks. We investigated the feasibility of localizing their booming calls, at a low frequency range between 100-200 Hz, using microphone arrays and robot audition HARK (Honda Research Institute, Audition for Robots with Kyoto University). We first simulated sound source localization of actual bittern calls for microphone arrays with radius sizes of 10 cm, 50 cm, 1m, and 10m, under different noise levels. Second, we monitored bitterns in an actual field environment using relatively small microphone arrays, in the Sarobetsu Mire, Hokkaido Island, Japan. Simulation results show that spectral detectability was higher for larger microphone arrays, whereas temporal detectability was higher for smaller microphone arrays. We found that false detection occurred in smaller microphone arrays, by a close distance to the transfer function for the opposite side, coincidentally generated in the calculation. Despite technical limitations, we successfully localized booming calls of at least two males in a reverberant wetland, surrounded by thick vegetation and riparian trees. This study provides the first case of localizing such rare birds using small-size microphone arrays in the field, thereby showing how this technology could contribute to auditory surveys of population numbers, behaviors, and microhabitat selection, all of which are difficult to obtain using any other observation methods. Not only is this methodology useful for better understanding bitterns, but can also be extended to investigate other rare nocturnal birds with low-frequency vocalizations, that are too timid to risk ringing or tagging. Our results also suggest a future need for a robust localization system to avoid reverberation and echoing in the field, resulting in false detection of the target birds.